2022
DOI: 10.3390/cells11162507
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Occurrence of E:N-cadherin Heterodimers in Adherens Junctions of Hepatocytes and Derived Tumors

Abstract: Cell–cell junctions are pivotal for embryogenesis and tissue homeostasis but also play a major role in tumorigenesis, tumor invasion, and metastasis. E-cadherin (CDH1) and N-cadherin (CDH2) are two adherens junction’s transmembrane glycoproteins with tissue-specific expression patterns in epithelial and neural/mesenchymal cells. Aberrant expression has been implicated in the process of epithelial–mesenchymal transition (EMT) in malignant tumors. We could hitherto demonstrate cis-E:N-cadherin heterodimer in end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Previous studies (82)(83)(84) have suggested that when cells undergo EMT and shift progressively from an epithelial to a mesenchymal state, genetic alterations include decreased expression levels of CDH1, cytokeratin 12 and TJP1, increased In conclusion, integrating the characteristics of biomarkers in multiple dimensions can ensure the most efficient management choice for each patient with cancer (Fig. 15).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies (82)(83)(84) have suggested that when cells undergo EMT and shift progressively from an epithelial to a mesenchymal state, genetic alterations include decreased expression levels of CDH1, cytokeratin 12 and TJP1, increased In conclusion, integrating the characteristics of biomarkers in multiple dimensions can ensure the most efficient management choice for each patient with cancer (Fig. 15).…”
Section: Discussionmentioning
confidence: 81%
“…We previously demonstrated that the co‐expression of E‐ and N‐cadherin is a characteristic of hepatocytes, cholangiocytes, and their derived tumors 17,18 . To test the potential of E‐ and N‐cadherin as markers in the differential diagnosis of PLC vs extrahepatic carcinomas, their expression was assessed in a total of 13,295 individual TMA cores comprised of 3359 different tumors (Tables 1 and 2), and compared to previously published analyses of 882 cases of PLC, including HCC and iCCA 17,18 . In a first step, we investigated E‐cadherin (Figure S1) and N‐cadherin (Figure 1) expression via immunohistochemistry (Tables 1, S2, and S3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, EMT, which is characterized by loss of E‐cadherin expression and increased expression of N‐cadherin, has been correlated with tumor invasion and metastasis 8,15 . In previous work, we showed that E‐ and N‐cadherin form cis‐E:N‐cadherin heterodimers in adherens junctions at the basolateral membrane of hepatocytes and cholangiocytes, 16 and that E‐ and N‐cadherin‐expression is retained in iCCA and HCC 17,18 . In fact, regardless of tumor grading, HCC show high N‐cadherin expression in 92% of cases, and co‐expression of E‐cadherin 17,18 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[53] Adherens junctions are known to have a significant impact on tumorigenesis, tumor invasion, and metastasis. [54,55] In addition, EGFR tyrosine kinase inhibitor compounds have shown remarkable efficacy in the treatment of different forms of leukemia that are highly resistant to conventional treatments. [56] FDA-approved tyrosine kinase-targeted therapies have been reported to overcome resistance in a specific subgroup of patients with APL who are unresponsive to standard treatment.…”
Section: Discussionmentioning
confidence: 99%